Search for the Decay of the Higgs Boson to Charm Quarks with the ATLAS Experiment - Alconada Verzini, María Josefina (2018)
A direct search for the standard model Higgs boson decaying to a pair of charm quarks is presented. Associated production of the Higgs and Z bosons, in the decay mode ZH → ℓ⁺ ℓ⁻ c͞c is studied. A data set with an integrated luminosity of 36.1  fb⁻¹ of pp collisions at √s = 13TeV recorded by the ATLAS experiment at the LHC is used. The H → c͞c signature is identified using charm-tagging algorithms. The observed (expected) upper limit on σ(pp → ZH) × B(H→ c͞c) is 2.7 (3.92.1-1.1) pb at the 95% confidence level for a Higgs boson mass of 125 GeV, while the standard model value is 26 fb.